The pragmatic particle ’áda in Kambaata (Cushitic) - Temesgen Senbeto Wadolo; Shimelis Mazengia (Journal of African Languages and Literatures)
This study investigates the morphological makeup, syntactic features and pragmatic functions of ’áda, a pragmatic marker (pm) in Kambaata (Cushitic). The data were drawn from a corpus of two hours of recorded, transcribed and annotated spontaneous speech. The pragmatic marker is a freestanding word. As a particle, it does not take any affixes except another pragmatically deter-mined suffix ‑be, which is used for negating one’s own or an interlocutor’s intention. The pm appears before or after a simple sentence and a complement clause. It may also come after the matrix clause, which follows the complement clause. An interrogative sentence preceded by the pm changes into a rhetorical one. With a cleft sentence, the pm occurs either preceding or following the first focused (copula) clause. In all cases, it is separated with a pause from the rest of the words and phrases in the syntactic structure. Thus, it is an unintegrated extra-sentential unit. The historical origin and the potential source from which the particle was grammaticalized could not be determined. Its functions include signaling repair, surprise, apology, noticing and turn yielding. In some contexts, more than one of the preceding functions can overlap.